Global Research Trends in Islamic Social Finance for Sustainable Development Goals (SDGs): A Bibliometric Analysis - Arlinta Prasetian Dewi; Majdy Kasheem (UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
Introduction: This study aims to analyze global research trends in Islamic Social Finance (ISF) related to the Sustainable Development Goals (SDGs) and identify emerging themes, collaboration patterns, and future research directions within this field. Research Methods: This study employed a quantitative bibliometric approach using the PRISMA framework. Data were collected from the Scopus database covering publications from 2020 to 2026. Following a systematic screening process, 123 publications were analyzed using VOSviewer. Results: The dominant research themes include sustainability, poverty alleviation, financial inclusion, zakat, waqf, and Islamic microfinance, while recent studies show a shift toward technology-driven themes such as Islamic fintech, blockchain, crowdfunding, ESG integration, and digital transformation. Conclusion: This study provides a comprehensive bibliometric mapping of global ISF research, highlighting the growing integration of Islamic Social Finance with digital technology, ESG frameworks, and sustainable finance, while identifying blockchain-based waqf, digital zakat ecosystems, and Islamic fintech for SDGs as promising directions for future research and policy development.